Meningitis TB Pada Anak 16 tahun: Laporan Kasus - Alghani, Sulthan Rafi; Nareswari, Shinta (Medula, 2024)
Tuberculous meningitis is a form of Mycobacterium tuberculosis infection that affects the meninges of the brain. The case discussed involves a 16-year-old male adolescent who initially presented with symptoms of headache, fever, neck pain, and neck stiffness, which persisted for several weeks. The delay in diagnosis occurred due to the similarity of the initial symptoms to bacterial meningitis, often leading to postponed TB treatment. The diagnosis was established through anamnesis, physical examination, and supporting tests, including a molecular rapid test (TCM) on cerebrospinal fluid (CSF) and a head CT scan, which confirmed the presence of miliary TB in the lungs and meningitis accompanied by hydrocephalus. The patient also experienced a weight loss of four kilograms over the past two weeks, indicating systemic signs of chronic infection. Although the patient received Anti-Tuberculosis Treatment (ATT) such as rifampicin, isoniazid, pyrazinamide, and ethambutol, his condition deteriorated, and he ultimately passed away on the ninth day of hospitalization. Neurological examination revealed a progressive decline in consciousness to a GCS score of 8 and the presence of pathological reflexes, such as a positive Babinski sign, confirming central nervous system involvement. The mortality rate of TB meningitis remains high due to delayed ATT caused by the lack of early diagnosis, emphasizing the importance of early detection to improve patient prognosis. Preventive efforts through active screening of high-risk groups and education about the early symptoms of TB meningitis are crucial in reducing morbidity and mortality rates.